2002
DOI: 10.1084/jem.20021052
|View full text |Cite
|
Sign up to set email alerts
|

CD4 Effector T Cell Subsets in the Response to Influenza

Abstract: The immune response of naive CD4 T cells to influenza virus is initiated in the draining lymph nodes and spleen, and only after effectors are generated do antigen-specific cells migrate to the lung which is the site of infection. The effector cells generated in secondary organs appear as multiple subsets which are a heterogeneous continuum of cells in terms of number of cell divisions, phenotype and function. The effector cells that migrate to the lung constitute the more differentiated of the total responding… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

41
320
8
1

Year Published

2004
2004
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 300 publications
(370 citation statements)
references
References 55 publications
41
320
8
1
Order By: Relevance
“…In vitro studies with human CMVspecific T cells showed that the antigen dose positively correlated with the CD70 expression levels that are induced [27]. Roman et al [50] showed that after influenza infection a broad spectrum of antigen-specific effector and memory CD4 + T cells emerge. Of these cells, the ones, which have undergone multiple divisions, are the cells that differentiate maximally into effector T cells and migrate to the lung and possibly other tertiary non-lymphoid sites [51].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In vitro studies with human CMVspecific T cells showed that the antigen dose positively correlated with the CD70 expression levels that are induced [27]. Roman et al [50] showed that after influenza infection a broad spectrum of antigen-specific effector and memory CD4 + T cells emerge. Of these cells, the ones, which have undergone multiple divisions, are the cells that differentiate maximally into effector T cells and migrate to the lung and possibly other tertiary non-lymphoid sites [51].…”
Section: Discussionmentioning
confidence: 99%
“…Of these cells, the ones, which have undergone multiple divisions, are the cells that differentiate maximally into effector T cells and migrate to the lung and possibly other tertiary non-lymphoid sites [51]. This homing pattern correlated with down modulation of CD62L and CCR7 and stable expression of CD44 and CD49d [50]. In vivo and in vitro studies with CD8 + T cells showed that total signal strength determines functional outcome of differentiation and acquisition of "fitness" [42,[52][53][54].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, Reinhardt et al [24] and Roman et al [26] found that it was the most highly divided cells that left lymphoid tissues, making it possible that our conclusions about cycling and survival were skewed by underrepresented populations of DO11.10 T cells. To determine whether or not migration of activated T cells out of secondary lymphoid tissues affected our findings, DO11.10 T cells in representative non-lymphoid organs were examined.…”
Section: Effects Of Tlr Agonists On Accumulation and Cycling Of Do11mentioning
confidence: 95%
“…Most animals depleted of both CD8 T cells and B cells are not able to clear the virus, which results in death (14,32,53). CD4 ϩ T cells certainly contribute to the control of IAV infection, although cytotoxic CD4 T cells are not frequently observed unless cultured in vitro (8,22,45). Thus, it is generally accepted that CD8 T cells and/or antibodies are sufficient for timely and complete IAV clearance.…”
mentioning
confidence: 99%